A new player in the game: platelet-derived extracellular vesicles in dengue hemorrhagic fever. (18th May 2020) - Perez-Toledo, Marisol; Beristain-Covarrubias, Nonantzin
Abstract: Thrombocytopenia and vascular leakage are clinical hallmarks in dengue hemorrhagic fever. Sung et al. present a new mechanism where platelet-derived extracellular vesicles participate in increasing vascular permeability during dengue virus infection in mice.